Korelasi lingkar leher terhadap kalsifikasi koroner lebih baik daripada IMT dan lingkar pinggang pada subyek obesitas resisten insulin - Antonia A Lukito; Andi Wijaya; Peter Kabo; Syakib Bakri (The Indonesian Heart Association, 2012)
The association of obesity, insulin resistance, and chronic low-grade inflammation has been evident for years. Neck circumference (NC), a parameter of subcutaneous fat, is a unique storage depot and allegedly has an additional role for cardiovascular risk beyond the effect of abdominal circumference.Vascular calfication is identified at early stage of atherosclerosis and associated with cardiovascular events. The degree of calcification associated with local vascular inflammation and progression of atherosclerosis, however, there is no study linking NC independently to coronary calcification, an established parameter of subclinical atherosclerosis. This study carried out 60 obese non-diabetes men, consisted of 30 insluin-resistant (IR) and 30 non insulin-resistant (NIR) subjects. In IR subjects, there was a significant positive correlation between CAC score with NC, but none between CAC score with body mass index (BMI) or waist circumference. A significant correlation was found between hs-CRP with CAC score or NC in IR subjects, but none in NIR subjects. Interestingly, the correlation between NC and CACA score in IR subjects remained significant after each of BMI, hs-CRP, HOMA-IR, leptin or adiponectin being adjusted, lead to suggestion of another mechanisms might invlolve in the patho-mechanisms of coronary calcification in upper body obesity subjects. We concluded, in non-diabetic beyond the effect of BMI, low-grade inflammation, the degree of insulin resistance and adipokines such as leptin and adipocnetin.